1991
DOI: 10.1121/1.401770
|View full text |Cite
|
Sign up to set email alerts
|

The use of prosody in syntactic disambiguation

Abstract: Prosodic structure and syntactic structure are not identical; neither are they unrelated. Knowing when and how the two correspond could yield better quality speech synthesis, could aid in the disambiguation of competing syntactic hypotheses in speech understanding, and could lead to a more comprehensive view of human speech processing. In a set of experiments involving 35 pairs of phonetically similar sentences representing seven types of structural contrasts, the perceptual evidence shows that some, but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
341
2
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(355 citation statements)
references
References 10 publications
7
341
2
5
Order By: Relevance
“…For example, Price, Ostendorf, Shattuck-Hufnagel, & Fong (1991) had speakers produce ambiguous sentences like those in (2) following a disambiguating context, and showed that speakers consistently place boundaries in different places depending on the intended meaning.…”
Section: Intonational Phrasingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Price, Ostendorf, Shattuck-Hufnagel, & Fong (1991) had speakers produce ambiguous sentences like those in (2) following a disambiguating context, and showed that speakers consistently place boundaries in different places depending on the intended meaning.…”
Section: Intonational Phrasingmentioning
confidence: 99%
“…Primarily, speakers mark boundaries with increased duration of pre-boundary words (Price, et al, 1991;Wightman, Shattuck-Hufnagel, Ostendorf, & Price, 1992;Ferreira, 1993;Lehiste, Olive & Streeter, 1976;Selkirk, 1984;Schafer, et al, 2000;Snedeker & Trueswell, 2003) and / or silence (Lehiste, 1973;Klatt, 1975;Cooper & Paccia-Copper, 1980). In addition, speakers often raise or lower their pitch at the end of intonational phrases (Streeter, 1978;Pierrehumbert, 1980).…”
mentioning
confidence: 99%
“…Evidence from a recent ERP study indicates that intonational boundaries are immediately decoded and used to guide the listener's initial decisions about a sentence's syntactic structure [Steinhauer et al, 1999;Steinhauer and Friederici, 2001]. Many studies have shown that attention to prosodic cues (i.e., F 0 and duration) can help listeners to distinguish between potentially ambiguous sentences, e.g., old (men and women) vs. (old men) and women [Baum and Pell, 1999;Price et al, 1991]. The types of slow F 0 movements that occur at phrasal boundaries can also give listeners some semantic information about the sentences they are listening to.…”
Section: Prosodic Information In Spoken Language Comprehensionmentioning
confidence: 99%
“…At the same time, prosody can signal a sentence's syntactic structure, evidenced by listeners' use of prosody to determine the intended interpretation of syntactically ambigous sentences (e.g. Kjelgaard & Speer, 1999;Marslen-Wilson, Tyler, Warren, Grenier, & Lee, 1992;Price, Ostendorf, Shattuck-Hufnagel, & Fong, 1991;Schafer, 1997;Snedecker & Trueswell, 2003;Speer, Kjelgaard, & Dobroth, 1996).…”
Section: Introductionmentioning
confidence: 99%